Biomasses of different Salix L. clones in the decarboxylation process during energy production - Urošević Jelena D.; Rodzkin Aleh I.; Jovanović Filip A.; Tadić Vojin M.; Trivan Goran Đ.; Stanković Dragica M. (Zbornik Matice Srpske za Prirodne Nauke, 2025)
Biomass is increasingly employed in diverse applications to achieve and enhance energy efficiency, owing to its carbon-neutral nature. This is attributed to the fact that the quantity of CO2 released during its combustion corresponds precisely to the amount absorbed by biomass during its growth. The objective of this study is to assess the energy efficiency of biomass derived from analysed clones of fast-growing willow species in co-combustion processes with lignite at varying percentage ratios. The primary goal is to enhance the calorific value of lignite, optimize combustion and mitigate the harmful effects of combustion. The obtained results indicate that the calorific value of willow is higher than the calorific value of coal. The calorific value of coal (lignite) depends on the location of the coal deposit (field), while the calorific value of willows depends on the type of willow. Notably, clones 347 and NS 73/6 of white willow (Salix alba), have the highest energy potential compared to clones B-44 of white willow and basket willow (Salix viminalis).